Superficial thrombophlebitis (Mondor′s Disease) after breast augmentation surgery - Viana Giovanni Andre; Okano Fabricio (Indian Journal of Plastic Surgery, 2008)
Although the aetiology of Mondor′s disease remains unclear, the most commonly cited cause is trauma of some sort. Although surgical trauma has frequently been quoted, reports that specifically implicate aesthetic breast surgery are unusual in the literature. In this article, the authors report a case of superficial thrombophlebitis of the anterolateral chest wall secondary to breast augmentation surgery in a woman, five months after the procedure. The authors performed an analysis of the disease′s main etiologic components and preponderant clinical aspects, and determined all appropriate therapeutic measures.